Elimination Diet Guided by Food-Specific IgG Antibodies Measurements in Chronic Adult Acne in Thailand: A Prospective RCT Study - Maiprasert, Mart; Khunngam, Pongsiri; Rakchart, Sarawalai; Tovanabutr, Napatra; Wanitphakdeedecha, Rungsima; Srinoulprasert, Yutthana; Chai-Adisaksopha, Chatree (International Journal of Statistics in Medical Research, 2024)
Background: Adult female acne is increasingly prevalent and significantly affects quality of life. Current treatments, including antibiotics and hormonal therapies, often yield varied efficacy and risks. While adult acne shares similarities with adolescent acne, its pathogenesis involves genetic, hormonal, immune, and dietary factors. Emerging research implicates high glycemic load diets, milk proteins, and insulin/IGF1 signaling in exacerbating acne. Despite growing understanding, dietary influences remain poorly understood, overshadowed by persistent myths. Inflammation, preceding follicular plugging and hyperkeratinization, suggests a potential shift towards addressing gut inflammation and digestive issues. IgG-mediated food reactions, linked to conditions like IBS and migraines, are controversial in diagnosing acne but warrant investigation, especially in Thai patients. Objective: Evaluate the efficacy of elimination diets guided by food-specific IgG antibodies measurement in chronic adult acne. Patients and Methods: This randomized controlled trial and prospective cohort study enrolled 75 participants with chronic acne aged 19 to 45 years, meeting stringent inclusion criteria. Participants were randomized into three groups: one receiving elimination diets based on reversed IgG antibody measurements, another on common food-specific IgG antibodies, and a third on individual IgG antibody measurements. Elimination diets were informed by Genarrayt™ 200+ Food IgG kit results, with compliance monitored through dietary checklists. Primary outcomes were assessed using the Global Acne Grading System (GAGS) Score, with secondary outcomes including the Thai version of the Dermatology Life Quality Index Questionnaire and a Multiorgan-Symptoms Checklist. Follow-ups were conducted at 2, 4, 8, and 12 weeks. Results: The study cohort, predominantly female (74.7%), exhibited a mean age of 29.3 ± 5.3 years and an average GAGS Score indicating moderate acne severity. Significant differences in GAGS Scores were found among groups (P<0.001), indicating reduced acne severity in the elimination diet groups. Statistically significant reductions in weight and BMI were observed in one group (p-values = 0.048), but not in the other groups. Compliance with follow-up criteria was high. Conclusion: Elimination diets guided by food-specific IgG antibodies measurement show promise in reducing chronic adult acne severity, as indicated by GAGS Scores. This study sheds light on the relationship between diet and adult acne pathophysiology, emphasizing the potential of personalized treatment approaches. Further research is warranted to validate these findings and elucidate underlying mechanisms.